2020
DOI: 10.31234/osf.io/2ruyn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical Regularities Shape Semantic Organization throughout Development

Abstract: Our knowledge about the world is represented not merely as a collection of concepts, but as an organized lexico-semantic network in which concepts can be linked by relations, such as “taxonomic” relations between members of the same stable category (e.g., cat and sheep), or association between entities that occur together or in the same context (e.g., sock and foot). To date, accounts of the origins of semantic organization have largely overlooked how sensitivity to statistical regularities ubiquitous in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 24 publications
(32 reference statements)
1
31
0
Order By: Relevance
“…This might be the case as language acquisition often starts later in children with CI. Unger et al [59] found evidence that links between words in the semantic network are influenced by co-occurrence. However, links between words based on co-occurrence can only be established after having received a sufficient amount of language input.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the case as language acquisition often starts later in children with CI. Unger et al [59] found evidence that links between words in the semantic network are influenced by co-occurrence. However, links between words based on co-occurrence can only be established after having received a sufficient amount of language input.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive evidence suggests that from early development into adulthood, semantic organization is shaped by associative semantic links. Associative links, such are those between apple, eat and juicy, connect concepts whose labels or real-world counterparts are often experienced together (Blaye, Bernard-Peyron, Paour, & Bonthoux, 2006;Fenson, Vella, & Kennedy, 1989;Lin & Murphy, 2001;Unger, Savic, & Sloutsky, 2020;Walsh, Richardson, & Faulkner, 1993).…”
Section: Two Critical Types Of Semantic Links: Associative and Taxonomicmentioning
confidence: 99%
“…For example, the link between apple and juicy can support inferring that mipp is a fruit upon hearing "mipp is juicy" (Sloutsky, Yim, Yao, & Dennis, 2017). These and other contributions of associative links to semantic organization emerge early in development (e.g., Blaye et al, 2006;Fenson et al, 1989;Sloutsky et al, 2017;Unger et al, 2020), and persist into adulthood (e.g., Kutas & Federmeier, 2000;Lin & Murphy, 2001;Sloutsky et al, 2017).…”
Section: Two Critical Types Of Semantic Links: Associative and Taxonomicmentioning
confidence: 99%
See 2 more Smart Citations